Products of complementation between temperature-sensitive mutants of simian virus 40. - Chou, J Y (1975)
Temperature-sensitive mutants of the D complementation group of simian virus 40 exhibit delayed complementation. Analysis of the thermal stability, kinetic profiles in temperature shift experiments, and progeny of complementation have led to the hypothesis that delayed complementation is not true complementation, but the result of a very low level of leakiness, followed by phenotypic mixing of the progeny D mutants. This hypothesis is consistent with the proposal that D mutants are defective in uncoating. In the course of these experiments, it was observed that fresh medium suppresses the growth of D mutants at the restrictive temperature.